Desafios na formação de competências para profissionais de ATER em áreas de assentamento e agricultura familiar: análise do Programa Residência Agrária - Garcia, Janisse Viero (2007)
As an attempt at promoting the approximation between the Universities and the social movements in order to qualify the processes of formation of technicians in Technical Assistance and Rural Extension (ATER), MDA/INCRA created the Agrarian Residence Program. The Agrarian Residence Program is a national coverage program; it is coordinated by MDA/INCRA Ministry of Agrarian Development/National Institute for Colonization and Agrarian Reform, and is developed in the North, Northeast, Mid-West and the South/Southeast regions of Brazil. The Federal University of Santa Maria (UFSM) joined the program as one of the program units in the South/Southeast region (with UFRJ, UNICAMP and UFPR). This work aimed at contributing to the identification of the challenges implied in the formation of professionals of higher education with a differentiated profile to work with family farmers and settlers, through a critical evaluation of the experience of the UFSM project. It attempts at explicitating the perception of the participants in the Agrarian Residence Program about their main difficulties in the formation of competences for the work of ATER in the Program scope. In order to reach the objectives, a qualitative research was done through a participant observation of the researcher in several activities of the course, and semi-structured interviews in the several stages of the course with the participant students in the Agrarian Residence Project of UFSM and the Program managers. It was observed that before the experiences and challenges placed in each stage, different reactions on the part of students are perceived, who basically decide for their permanence or not in the project, as well as face or not the challenges of learning. It is understood that such dynamics determines differences in the individual trajectories and in the progress in terms of formation of competences made in the project. Such interpretation reveals the importance and central role of the subjects decisions in the improvement of the learning processes and, as a consequence, it indicates that the progress was differentiated from individual to individual.